2017
DOI: 10.1038/s41598-017-08214-4
|View full text |Cite
|
Sign up to set email alerts
|

Responses of crop yield growth to global temperature and socioeconomic changes

Abstract: Although biophysical yield responses to local warming have been studied, we know little about how crop yield growth—a function of climate and technology—responds to global temperature and socioeconomic changes. Here, we present the yield growth of major crops under warming conditions from preindustrial levels as simulated by a global gridded crop model. The results revealed that global mean yields of maize and soybean will stagnate with warming even when agronomic adjustments are considered. This trend is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 43 publications
8
147
0
2
Order By: Relevance
“…Liu et al () and Zhao et al () recently showed that up‐scaled simulations for representative locations, as suggested by van Bussel et al (), have similar temperature impacts to 0.5 o x 0.5 o global grid simulations or statistical approaches. The projected impact for spring wheat reported here is similar to that reported by Iizumi et al (), who reported global spring wheat production to increase by 1.43%–1.60% and 1.43%–1.61% under 1.5 and 2.0 scenarios using a global gridded simulation approach under different Shared Socioeconomic Pathways.…”
Section: Discussionsupporting
confidence: 88%
“…Liu et al () and Zhao et al () recently showed that up‐scaled simulations for representative locations, as suggested by van Bussel et al (), have similar temperature impacts to 0.5 o x 0.5 o global grid simulations or statistical approaches. The projected impact for spring wheat reported here is similar to that reported by Iizumi et al (), who reported global spring wheat production to increase by 1.43%–1.60% and 1.43%–1.61% under 1.5 and 2.0 scenarios using a global gridded simulation approach under different Shared Socioeconomic Pathways.…”
Section: Discussionsupporting
confidence: 88%
“…Worldwide, historical crop yield trends have more commonly shown reductions rather than increases due to climate change even though the atmospheric CO 2 concentration has been increasing (Porter et al 2014). Global and regional studies mostly indicated yield reductions for wheat and maize, especially in low latitudes (Bassu et al 2014, Porter et al 2014, Rosenzweig et al 2014, Asseng et al 2015, Zhao et al 2017, and many results found that limiting warming to 1.5°C would result in less severe negative impacts on wheat and maize yields than at 2.0°C (Schleussner et al 2016, Huang et al 2017, Iizumi et al 2017. Interestingly, a recent study (Ruane et al 2018) found that yields for the C 3 crops including wheat improve in nearly all regions around the world for a 2.0°C warmer world as CO 2 effects would offset the negative impacts of increasing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, water availability for irrigation may become an increasingly critical limiting factor (Scanlon et al, 2012). Notably, in most assessments of climate change impacts on crops, maize stands out to be the most negatively affected (Deryng et al, 2014;Iizumi et al, 2017;Tebaldi & Lobell, 2018).…”
Section: 1029/2018ef000995mentioning
confidence: 99%